Requirement for Ergosterol in Berberine Tolerance Underlies Synergism of Fluconazole and Berberine against Fluconazole-Resistant Candida albicans Isolates - Xu, Yi; Quan, Hua; Wang, Yan; Zhong, Hua; Sun, Jun; Xu, Jianjiang; Jia, Nuan; Jiang, Yuanying (Frontiers in Cellular and Infection Microbiology, 2017)
Candida albicans is one of the most common fungal pathogens. Our previous study demonstrated that concomitant use of berberine (BBR) and fluconazole (FLC) showed a synergistic action against FLC-resistant C. albicans in vitro and BBR had a major antifungal effect in the synergism, while FLC played a role of increasing the intracellular BBR concentration. Since the antifungal activity of BBR alone is very weak (MIC > 128 μg/mL), it was assumed that FLC-resistant C. albicans was naturally tolerant to BBR, and this tolerance could be reversed by FLC. The present study aimed to elucidate the mechanism underlying BBR tolerance in FLC-resistant C. albicans and its disruption by FLC. The ergosterol quantitative analysis showed that the BBR monotreatment could increase the content of cellular ergosterol. Real-time RT-PCR revealed a global upregulation of ergosterol synthesis genes in response to BBR exposure. In addition, exogenous ergosterol could decrease intracellular BBR concentration and increase the expression of drug efflux pump genes, further reducing the susceptibility of C. albicans to BBR. Similar to FLC, other antifungal agents acting on ergosterol were able to synergize with BBR against FLC-resistant C. albicans. However, the antifungal agents not acting on ergosterol were not synergistic with BBR. These results suggested that ergosterol was required for BBR tolerance, and FLC could enhance the susceptibility of FLC-resistant C. albicans to BBR by inhibiting ergosterol synthesis.